Analysis of BPJS Patient Registration in the Emergency Room Using the FRISTA Application at Hospital X Bandung City - cahyadi, Dhila Choirunnisa; Yuyun Yunengsih (International Journal of Psychology and Health Science, 2025)
This study aims to evaluate the effectiveness of the use of the FRISTA (Face Recognition Intergrated System Hospital) application in the registration process of BPJS patients at the Emergency Department (IGD) of Bandung City Hospital. This study uses a qualitative descriptive method using data collection techniques through observation, interviews, and documentation involving registration officers and medical record officers in the emergency room. The results obtained show that the application of FRISTA can speed up the patient registration process and prevent misuse of participant data. However, there are still some technical obstacles in the field, such as biometric verification failures using face ID caused by inadequate lighting, the use of masks, and frequent internet network disruptions. Therefore, hospitals are advised to carry out regular system maintenance, improve network quality, improve security systems, and ensure hardware and software readiness to ensure system reliability in all related units.